A review of literature on benefits of taper phase for main competition of periodization model in endurance athletes - Jae-Ryang Yoon (Korea Institute of Sport Science, 2020)
Purpose The aim of this study was to provide athletes and coaches on informations and benefits of a taper through evidence-based scientific studies and literatures in order to optimize an athlete's top performance for the major competition. Methods Studies and literatures search was conducted using the databases RISS, KISS, SPORTDiscuss. Key words searched: taper AND(competition, OR performance, OR training, OR training). This study were eventually cited by 22 articles for results of this in total 100 articles. Results The training load is remarkably reduced during a taper. With a reduced training load, training intensity should be maintained during the taper. The training load reductions during the taper should be programmed with reducing training volume at 41% to 60% of pretaper training. The reduction of training frequency during a taper means that affect moderately trained athletes and highly trained subjects differently, reducing 30% to 50% of pretaper training and maintaining training frequencies, respectively. Detraining the duration of a taper is not easy. Most athletes is beneficial from a 2-week shorter or longer tapers, depending on their individual profiles of fitness loss, fatigue dissipation, and anxiety. The manipulations of this training program variables usually affect for most athletes and maximal performance gains. Conclusion Training intensity should be maintained during the taper, training volume reductions should be programmed at 41% to 60% of pretaper training. The reduction of training frequency could be reduced 30% to 50% of pretaper training, and most athletes is beneficial from a 2-week shorter or longer tapers. Future researches should be conducted the practical & effectual differences in individual and teamed-based sports after a taper procedure.